TAX COMPLIANCE COST: EXPLORE BODY OF LITERATURE BY USE SCIENCE MAPPING - Dekar Urumsah; Rafi'i Habib Al Rasyid (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2023)
This research aims to explore the knowledge base of tax compliance cost research. Sample literature was taken through the Scopus database. The sample consists of 67 literatures on tax compliance costs with coverage from 1978 to 2021. This research uses systematic literature review, science mapping, and bibliometric analysis methods. Content analysis is carried out to understand in depth the current research topic. In general, the results of the study conclude that research on tax compliance costs needs to go to beyond the complexity of taxation. This research contributes to help academic researchers, policy maker, and regulators potraiying the complete picture of this research area and allow them to formulate furthure research and evidance base policy.